The liquidity of the government bond market - What impact does quantitative easing have? Evidence from Sweden - Marianna Grimaldi; Alberto Crosta; Dong Zhang (Sveriges Riksbank, 2021)
We consider the effects of quantitative easing on the liquidity of the Swedish government bonds. To capture multiple dimensions of liquidity we use several measures built on a unique and highly granular transaction-based dataset. We find that the Riksbank's purchases of government bonds improved liquidity, but only to a point. In fact, the deterioration in the level of market liquidity from quantitative easing via the scarcity effect is significantly larger than the improvement from the demand effect. We find that such effects are nonlinear; they tend to be amplified when the share of the central bank holdings is larger than a threshold (40 percent).
Keywords: E52; E58; G12; 330; Market Liquidity; Government Bond Market; Quantitative Easing; Public Debt Management